The Use of A Collaborative Learning Strategy of Think-Pair-Share by Listening to An English Dialogues to Improve Learning Outcomes - Dadan Zulkifli (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sulawesi Tenggara, 2023)
This study aims to improve cadet learning outcomes through the application of cooperative learning model. The subject of this study is a cadet of the TPS study program batch 58 of the Jakarta Technical University of Fisheries for the 2022/2023 academic year. This class consists of 39 cadets with a cadet composition, namely 10 female cadets and 19 male cadets. This cadet was chosen as a research subject because this cadet has a low ability to understand listening before. The object of this study is the result of learning to listen to short English dialogues. The location of this research is in the class of cadets of the TPS study program batch 58 of the Jakarta Fisheries Polytechnic. The study was based on preliminary observations that indicated cadets had problems listening. In accordance with the purpose of this study, which is to improve learning outcomes in listening, this research was carried out in the form of classroom action research. This class action research is described in a cyclical or spiral process consisting of several steps, namely planning, action, observation, and reflection. This class action research is carried out in 2 cycles. Each cycle consists of three sessions of which two sessions are for action and one session for testing. The results of this study showed that the learning outcomes of listening to cadets increased by applying the Think Pair Share (TPS) type or cooperative learning model. This can be seen from the average score of cadets in the test. The average score of cadets in the pre-test was 48.27. Then it increased to 72.75 in cycle I (one). This result is not satisfactory because it has not met the completeness criteria that have been targeted by researchers. The results of cadet scores increased after researchers modified teaching and learning activities in cycle II. As a result, the average score of cadets has increased to 86.20 and 93% of cadets have achieved learning completion, which means that it has exceeded the target of 75%. It can be concluded that the application of the cooperative learning model can improve the listening ability of cadets from the results of the study.